The Impact of Internal Determinants and Environment on Market Orientation of Businesses from Slovak Foodstuff Industry - Salyova, Simona; Taborecka-Petrovicova, Janka (International Review of Management and Marketing, 2017)
In the context of highly competitive global markets, changing customer needs, increasing dynamics of business environment, growing quality of products and the other factors managers try to identify and apply the most suitable and effective theories whose enforcement will lead to superior performance. Market orientation is a concept that has appeared as a significant predictor of business performance and has presumed to ensure competitive advantage. The degree of market orientation differs from one business to another. In fact, the extent of market-oriented behaviour in business is affected by internal determinants and environment. Therefore, we focus our attention on studying various factors forming market-oriented behaviour. The aim of this article is to examine the impact of internal determinants and environment on market orientation of businesses from foodstuff industry in Slovakia. This study is a part of complex research which was focused on investigating the relationship between market orientation and business performance. Results presented in this paper may help businesses to identify crucial determinants that form market-oriented behaviour and finally contribute to improvement of business performance. Keywords: market orientation; business performance; market-oriented behaviour; foodstuff industry; determinants of market orientation. JEL Classifications: L110, L250, L660